Disorders of Psychological Adaptation of Patients with Impaired the Locomotor System - Galachenko, A. (Psychiatry, Neurology and Medical Psychology, 2016)
Investigation of the features of psychological adaptation disorder of patients with disorders of the locomotor system. The kinds of pathologies disorders the locomotor system and attendant non-psychotic mental disorders. Correction of mental disorders, including depression and psychotic level, have this kind of patients depends on the personality characteristics of the patient, the individual psychological defense mechanisms.